2017
DOI: 10.1177/1057083717699650
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of State Music Education Certification and Licensure Practices in the United States

Abstract: Teacher certification and licensure practices for music educators vary by state. Enhancing music teacher educator knowledge of state music education certification and licensure practices can inform music teacher preparation and improve future music teacher quality. The purpose of this study was to compile relevant information for music educators about the certification practices of each of the United States and the District of Columbia as of January 2016, and to examine the commonalities and differences among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…In today’s schools, music educators can expect to teach a variety of learners. Across the United States, nearly all music educators are certified to teach a broad range of grades and content areas (May et al, 2017). 1 Music teacher education program accreditation guidelines also state that “attention should be given to .…”
mentioning
confidence: 99%
“…In today’s schools, music educators can expect to teach a variety of learners. Across the United States, nearly all music educators are certified to teach a broad range of grades and content areas (May et al, 2017). 1 Music teacher education program accreditation guidelines also state that “attention should be given to .…”
mentioning
confidence: 99%
“…The practice was developed in 1954 at the University of Illinois; instrumental, choral, and general music tracks were established in order to reduce the number of credit hours and time needed in a certification program (Groulx, 2016; Kuhn, 1955). In contradiction with tracked music teacher education programs, most music teachers receive comprehensive licensure (May, Willie, Worthen, & Pehrson, 2017). While having discrete tracks of music teacher education streamlined the preparation process, as the current study explored, the specificity may not always adequately prepare teachers for the broad range of teaching experiences they will likely encounter in the field or for which they are certified.…”
mentioning
confidence: 99%
“…Based on current hiring practices of non-string specialists and the potential need of additional string educators in the future, it may be critical to provide support for non-string specialists who are assigned to teach string classes. Regardless of a teacher’s expertise or skill in a specialized music field, 39 states offer music teacher certification in which teachers would be considered qualified to teach strings, band, choir, general music, or any other type of music class (May, Willie, Worthen, & Pehrson, 2017). Research has suggested that teachers’ subject matter preparation and pedagogical training are positively related to student learning (Goldhaber & Brewer, 1997; Monk, 1994), and when teachers are assigned subjects outside their fields of specialty, both their instructional strategies and student learning gains are affected negatively (Goldhaber & Brewer, 1997; Monk, 1994; Ross, Cousins, Gadalla, & Hannay, 1999).…”
mentioning
confidence: 99%